Some extremal problems on the Riemannian sphere - Denega, I.V.; Zabolotnyi, Ya.V. (Carpathian Mathematical Publications, 2024)
In the paper, the open problem on maximum of the product of inner radii of n domains in the case, when points and domains belong to the unit disk, is investigated. This problem is solved only for $n=2$ and $n=3$. No other results are known at present. We obtain the result for all $n \geqslant 2$. Also, we propose an approach that allows to establish evolutionary inequalities for the products of the inner radii of mutually non-overlapping domains.